Penerapan Metode Communicative Approach Dalam Pembelajaran Bahasa Inggris Melalui Perangkat Multimedia Pada Siswa Kelas 11 (Penelitian Tindakan Kelas di SMKN 4 Palembang) - Yuspar Uzer; Yus Vernandes Uzer (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The communicative approach method also needs to emphasize how a teacher functions during the learning process, because the point of learning is to help students acquire the experience they need so that they can interact verbally and face-to-face by listening, retaining information or problem-solving. This method is a form of learning teaching that excels the existence of interaction between the teacher and the student.Based on that, we intend to propose a research entitled Commucicative Method Approach In Learning English Through Multimedia Devices In Grade 11 Students 4 Moist). With the theme of Application of Commucicative Approach in Learning English Through Multimedia Devices in Grade 11 Students (Research of Class Action In SMKN 4 Palembang) it can be concluded that the learning results of speaking skills and learning activities App English Language Learning Through Multimedia Devices In Grade 11 Students (Class Action Research In SMKN 4 Palembang) experienced improvement. The study was implemented with two cycles, the mean score obtained by the students after following the final test from cycle I to cycle II after applying the learning method underwent an increase i.e. from 62 in cycle I to 94 in cycle II from the ideal score that students could achieve learning ISpeaking skills 100. also experienced improvement. On cycle I, out of 10 (40%) students became on cycle II as many as 24 (96%) students achieved learning dropout and classical learning dropout was achieved. Students’ learning activities from the beginning of cycle I learning to with the end of cycle II learning experienced a positive improvement..